ANALISA KINERJA KEUANGAN UNTUK KEPUTUSAN PEMBERIAN KREDIT PADA BANK MANDIRI KCP BELAWAN - Hans Sebastian Sejahtera Siahaan; Ramadhan Harahap (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This research aims to determine the influence of Financial Performance Analysis on Credit Granting Decisions at Bank Mandiri KCP Belawan. This research uses a qualitative descriptive research method. Data collection techniques through observation, interviews and documentation. The results of this research are that the factors that can make a credit application accepted by the bank are (1) the debtor already has an official business license and NPWP, (2) the debtor must have 50% capital before applying for credit and the business is managed directly by the debtor himself. , (3) The debtor must be cooperative and open when asked about his efforts to arrange credit, (4) The debtor has never had a history of arrears in payments. (5) The debtor has never been involved in legal problems, (6) The value of the collateral provided by the debtor must be in accordance with the market price when applying for credit, (7) The established business has been running for approximately 1 year, (8) The business location is convenient accessible to local residents. If a business has no debt (current debt = 0), neither the current ratio nor the quick ratio can be calculated in the usual way and is considered undefined or infinite, then this shows that the business has a very strong liquidity condition because there are no liabilities. short term needs to be met.